2022
DOI: 10.1039/d2qi00226d
|View full text |Cite
|
Sign up to set email alerts
|

Nickel–salen as a model for bifunctional OER/UOR electrocatalysts: pyrolysis temperature–electrochemical activity interconnection

Abstract: The nickel derivative of a salen-type Schiff base is pyrolyzed under controlled conditions to form a nano-size Ni/NiOx core-shell species that serves as a model for a proof-of-concept investigation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…As shown in the XANES results (Figure e and Figure S19), the absorption edge of NiMOF/BP-240 has exhibited a redshift and thus a decrease of Ni valence compared to NiMOF. The near-absorption edge position of NiMOF/BP-240 lies between NiMOF (Ni 2+ ) and Ni foil (Ni 0 ), showing a coincidence with the XPS valence results (Ni δ+ and Ni 2+ states, Figure d) . From the XANES data, the average Ni valence in NiMOF/BP-240 was calculated as +1.61, suggesting the Ni δ+ of the cationic state rather than Ni 0 (supplemental note for Figure S20).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…As shown in the XANES results (Figure e and Figure S19), the absorption edge of NiMOF/BP-240 has exhibited a redshift and thus a decrease of Ni valence compared to NiMOF. The near-absorption edge position of NiMOF/BP-240 lies between NiMOF (Ni 2+ ) and Ni foil (Ni 0 ), showing a coincidence with the XPS valence results (Ni δ+ and Ni 2+ states, Figure d) . From the XANES data, the average Ni valence in NiMOF/BP-240 was calculated as +1.61, suggesting the Ni δ+ of the cationic state rather than Ni 0 (supplemental note for Figure S20).…”
Section: Resultsmentioning
confidence: 86%
“…51 Such a new Ni δ+ state is found only in the 3d). 54 From the XANES data, the average Ni valence in NiMOF/BP-240 was calculated as +1.61, suggesting the Ni δ+ of the cationic state rather than Ni 0 (supplemental note for Figure S20). The broadened and weakened white lines indicate the reduction in the Ni−O coordination number after combining NiMOF with BP (Figures S21 and S22).…”
mentioning
confidence: 99%
“…The six ligands are interlaced in the space, this implies that the conductive channel will be formed by the ligand after carbonization at high temperature. The Schiff base ligands have strong reducibility in previous research work, [ 5,13 ] referring to molecular clusters construction features, indicating that the Ni–Fe clusters are more benefit to the formation of alloys after carbonization at high temperature. We further performed thermogravimetric (TG) and Powder X‐ray diffraction (PXRD) to confirm the formation of alloys.…”
Section: Resultsmentioning
confidence: 99%
“…ICP (Table S4, Supporting Information) and Raman characterization revealed that the metal content and carbon type are still changing during the high temperature process after 400 °C, further demonstrating that the pyrolytic evolution is still going on at the smaller nanoscale. [ 13 ] The molecular structure undergoes a dramatic transformation after the first stage pyrolysis, which lays an important foundation for obtaining complex stable carbon network nanostructure with abundant reaction sites.…”
Section: Resultsmentioning
confidence: 99%
“…So far, the mainstream systems for studying electron/ion transport performance materials are perovskite materials, 5 inorganic 3d transition metal oxides/chalcogenides/nitrides, [6][7][8] metal organic frameworks (MOF), etc. [9][10][11][12][13][14][15] These material systems have made great progress in the study of electron/ion transport properties, providing us with extensive experience in optimizing the structure of electron/ion transport properties through the development and in-depth study of one of the material systems. Of note, manganese oxide provides a good material platform for the regulation of novel electronic states due to its easy regulation property.…”
Section: Introductionmentioning
confidence: 99%